Expressing infinite matrices as sums of idempotents - Słowik, R. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
Let $\scr M_{Cf} (F)$ be the set of all column-finite $N × N$ matrices over a field $F$. The following problem is studied: whatelements of $\scr M_{Cf} (F)$ can be expressed as a sum of idempotents? The result states that every element of $\scr M_{Cf} (F)$ canbe represented as the sum of 14 idempotents.